Back in fashion : western fashion from the Middle Ages to the present - Riello, Giorgio (Yale University Press, 2020)
This engaging volume tells the history of Western fashion, exploring how and why it has influenced people's attitudes, actions, and beliefs since the Middle Ages. Back in Fashion focuses on themes specific to particular periods, such as the significance of medieval sumptuary laws that limited expenditure on clothing, the use of black in early modern Europe, the role of sports on clothing in contemporary times and the rise of luxury in the new millennium. Author Giorgio Riello investigates how fashion has shaped and continues to characterize Western societies, impacting the lives of millions of people and their relationship to the economy and politics. Making a masterful case for why fashion history demands academic consideration on par with other more traditional histories, Riello presents fashion as a complex and constantly evolving force that not only reflects but drives cultural transformation.